Non-invasive Investigations for the Diagnosis of Fontan-Associated Liver Disease in Pediatric and Adult Fontan Patients - Fidai, Amyna; Dallaire, Frederic; Alvarez, Nanette; Balon, Yvonne; Clegg, Robin; Connelly, Michael; Dicke, Frank; Fruitman, Deborah; Harder, Joyce; Myers, Kimberley; Patton, David J.; Prieur, Tim; et al. (Frontiers in Cardiovascular Medicine, 2017)
Fontan-associated liver disease (FALD) is a serious complication related to the chronically elevated venous pressure and low cardiac output of this abnormal circulation. However, diagnostic markers for this condition are limited. We hypothesized that specific tests for fibrosis developed for other chronic liver diseases would identify a higher prevalence of FALD than ultrasound and standard laboratory tests and that identified abnormalities would correlate with time post-Fontan. In this cross-sectional study, we assessed 19 children (average age 8.4 ± 4.3 years and 5.4 ± 4.1 years post-Fontan) and 8 adults (average age 31.5 ± 8.9 years and 21.1 ± 4 years post-Fontan) using standard serum laboratory investigations assessing hepatic integrity and function, the FibroTest, liver ultrasound and transient elastography (FibroScan). In adult Fontan patients, hemoglobin, C-reactive protein and gamma glutamyl transpeptidase were significantly increased and white blood cell and platelet counts were significantly decreased in comparison to the pediatric cohort. International normalized ratio was mildly elevated in both children and adults. FibroTest results were suggestive of cirrhosis regardless of time post-Fontan. FibroScan measurements were significantly correlated with time post-Fontan but the frequency of ultrasound-detected liver abnormalities were not. No cases of hepatocellular carcinoma were identified. Abnormalities suggestive of FALD occur in both children and adults post-Fontan. Select laboratory tests, and possibly ultrasound and FibroScan in some patients, appear to have the most promise for the non-invasive detection of FALD.